(untitled) - Dieho, Kasper (Netherlands, 2017)
The objective of this thesis was to study the adaptation of the rumen to ration changes during the dry period and early lactation. Changes in rumen papillae morphology, fractional absorption rate of VFA (kaVFA), and changes in the composition of the rumen microbiota were the primary targets for study. In addition, the expression of genes and proteins associated with absorption and metabolism of VFA by the rumen epithelium were studied to better understand the relationship between functional changes and morphological changes of the papillae. Uniquely, all these aspects were studied in parallel in the same dairy cows during the dry period and early lactation using a repeated measurement setup. Two experiments were conducted. In the lactation experiment, the effect of transition from the dry period to the subsequent lactation, and the effect of early lactation concentrate build-up strategy on the adaptation of the rumen were studied. In the dry period experiment, the effect of feeding supplemental concentrate during the late dry period in order to ‘prepare’ the rumen for the lactation was studied.
Keywords: Bò sữa,Dairy cattle; Chăn nuôi,Breeding